High-strength pet net tube and method for manufacturing the same

CN122980065APending Publication Date: 2026-10-27HUIZHOU GUSHANG TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611084930.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,在需要承受频繁拖拽、动态弯折和复杂电磁环境的严苛工况下,常规pet编织网管的力学强度难以满足高可靠性要求

Benefits of technology

本发明的高强度pet网管可广泛应用于汽车线束保护、电子电器内部布线、通讯线缆整理及工业机器人管线包覆等领域。通过在pet纤维中引入核壳增强剂和改性掺铝氧化锌,赋予网管卓越的综合性能,核壳增强剂在受力时能够有效吸收冲击能量并阻止微裂纹扩展,从而显著提升网管的拉伸强度、抗撕裂性和耐动态疲劳性能;同时,改性掺铝氧化锌赋予网管高效且持久的抗静电能力,可及时耗散表面静电,避免灰尘吸附和静电放电对敏感电子元件的损害,保障设备运行安全。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of high polymer materials, and discloses a high-strength pet net tube and a preparation method thereof. The high-strength pet net tube comprises the following raw materials in parts by weight: pet chips 60-80 parts, a core-shell reinforcing agent 8-15 parts, nano high-clay 2-4 parts, triphenyl phosphate 1-2 parts, zinc stearate 3-6 parts, an antioxidant 0.5-1 part, and modified aluminum-doped zinc oxide 1-3 parts. The core-shell reinforcing agent can effectively absorb impact energy and prevent micro-crack propagation when being stressed, so that the mechanical properties of the net tube are remarkably improved. The modified aluminum-doped zinc oxide endows the net tube with efficient and durable antistatic capacity, can dissipate surface static electricity in time, and guarantees the safe operation of equipment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer materials technology, specifically to a high-strength PET mesh tube and its preparation method. Background Technology

[0002] Polyethylene terephthalate (PET) fiber is a semi-crystalline thermoplastic polyester fiber produced by esterification, polycondensation, and melt spinning of purified terephthalic acid and ethylene glycol as monomers. PET braided tubing, made from PET monofilaments or multifilaments through a weaving process, is often used as a bundled protection and mechanical protective jacket for wires and cables in electronic and electrical equipment due to its lightweight, flexibility, and abrasion resistance. However, under harsh operating conditions requiring frequent dragging, dynamic bending, and complex electromagnetic environments, the mechanical strength of conventional PET braided tubing is insufficient to meet high reliability requirements. In the braided structure, there is a significant stress concentration effect at fiber intersections, and the relatively smooth surface of PET fibers limits the cohesion and interfacial friction, resulting in insufficient overall tensile and tear strength of the tubing. Furthermore, the inherent high insulation of PET material leads to a significant problem of static electricity accumulation; during processing and use, static charge is easily generated and accumulated due to friction and peeling. In sensitive scenarios such as automotive electronics and industrial control, electrostatic discharge may damage or even break down precision electronic components, or pose a potential explosion hazard in flammable gas environments. Summary of the Invention

[0003] To address the aforementioned technical problems, this invention provides a high-strength PET mesh tube and its preparation method.

[0004] The objective of this invention can be achieved through the following technical solutions: A high-strength PET mesh tube comprises the following raw materials in parts by weight: 60-80 parts PET chips, 8-15 parts core-shell reinforcing agent, 2-4 parts nano-kaolin, 1-2 parts triphenyl phosphate, 3-6 parts zinc stearate, 0.5-1 part antioxidant, and 1-3 parts modified aluminum-doped zinc oxide. The antioxidant is at least one of antioxidant 1010, antioxidant 168, and antioxidant 1076; The core-shell reinforcing agent is prepared by the following steps: Step A1: Mix multi-walled carbon nanotubes (MWCNTs) treated with mixed acid with anhydrous ethanol, sonicate for 20 min, and purge with nitrogen for 5 min. Then, while stirring, add glacial acetic acid and 3-mercaptopropyltrimethoxysilane dropwise and react at room temperature for 24 h. After the reaction is complete, add acetone and continue to react under a nitrogen atmosphere for 6 h. After filtration, washing, and vacuum drying, obtain thiol-modified MWCNTs, i.e., SH-MWCNTs. Furthermore, the ratio of MWCNTs, anhydrous ethanol, glacial acetic acid, 3-mercaptopropyltrimethoxysilane and acetone is 0.4g:100mL:4-5mL:8-10mL:100-120mL; In step A1, 3-mercaptopropyltrimethoxysilane is grafted onto the surface of MWCNTs to provide reaction conditions for the subsequent thiol-ene click reaction. MWCNTs can improve the strength and elastic modulus of PET fibers. When the fiber is under stress, the stress will be transferred from the PET matrix to the MWCNTs, and the MWCNTs will bear the main tensile force.

[0005] Step A2: Add vinyl-POSS solution to SH-MWCNTs, then add azobisisobutyronitrile (AIBN), stir, bubble with nitrogen for 20 min, heat to 80°C in an oil bath, stir and react for 8 h under nitrogen protection, cool to room temperature, filter, wash with toluene and anhydrous methanol successively, and dry under vacuum to obtain POSS@MWCNTs; Furthermore, the vinyl-POSS solution is prepared by mixing vinyl-POSS and toluene at a volume ratio of 0.1-0.2 g: 20-30 mL; Furthermore, the ratio of vinyl-POSS solution, SH-MWCNTs, AIBN, toluene, and anhydrous methanol is 20-30 mL: 0.4 g: 0.0015-0.0025 g: 20-40 mL: 15-30 mL; In step A2, vinyl-POSS and SH-MWCNTs undergo a thiol-ene click reaction. The introduced double bond provides the reaction conditions for subsequent reactions. The introduced POSS molecule can induce PET crystallization, increase the crystallization rate and crystallization temperature, and its steric hindrance can weaken the van der Waals forces between MWCNTs, inhibit MWCNT aggregation, and make it more uniformly dispersed in the PET melt, thereby improving the fiber's fracture toughness while increasing its strength.

[0006] Step A3: Mix POSS@MWCNTs and toluene, add 1-thioglycerol and AIBN, react at 80°C for 12 h under nitrogen protection, cool to room temperature, filter, wash, and vacuum dry to obtain OH-POSS@MWCNTs; Furthermore, the ratio of POSS@MWCNTs, toluene, 1-thioglycerol, and AIBN is 0.4 g : 20-30 mL : 0.2-0.4 g : 1.5-3 mg; In step A3, the double bonds on the surface of POSS@MWCNTs undergo a thiol-ene click reaction with 1-thioglycerol, introducing hydroxyl groups into the system and providing reaction conditions for subsequent polymerization.

[0007] Step A4: Mix OH-POSS@MWCNTs and ethylene glycol, sonicate for 5 min, then add dimethyl terephthalate and zinc acetate catalyst, stir and heat to 185℃ for reaction, react for 3 h, add antimony trioxide condensation catalyst, continue heating to 200℃, evacuate to 15 Pa, keep at this temperature for 1 h, then raise the temperature to 285℃ for condensation, stop the reaction when the system viscosity reaches 0.7 dL / g, cool, wash with anhydrous ethanol, vacuum dry to obtain core-shell reinforcing agent; Furthermore, the ratio of OH-POSS@MWCNTs, ethylene glycol, dimethyl terephthalate, zinc acetate, antimony trioxide, and anhydrous ethanol is 0.4g: 13-15mL: 0.4-0.5g: 0.004-0.005g: 0.004-0.005g: 30-50mL; In step A4, ethylene glycol and dimethyl terephthalate are polymerized in situ on the OH-POSS@MWCNTs surface to form PET. The PET matrix structure is consistent with the PET matrix structure, and the compatibility is excellent. This helps to eliminate interfacial defects. The synergistic effect with POSS and MWCNTs makes the filler more uniformly and stably dispersed in the PET matrix, ensuring the uniformity of fiber mechanical properties.

[0008] The modified aluminum-doped zinc oxide is prepared by the following steps: Step B1: Prepare 0.15 mol / L zinc sulfate aqueous solution, 0.15 mol / L aluminum ammonium sulfate aqueous solution and 0.45 mol / L ammonium bicarbonate aqueous solution respectively. Under the conditions of stirring, reaction temperature of 50℃ and pH of reaction solution of 7, add ammonium bicarbonate aqueous solution to aluminum ammonium sulfate aqueous solution, followed by zinc sulfate aqueous solution. After aging for 12 h, filter, wash, dry, grind, and then put into a muffle furnace and keep at 500℃ for 2 h to obtain intermediate product 1. Furthermore, the ratio of zinc sulfate aqueous solution, aluminum ammonium sulfate aqueous solution, and ammonium bicarbonate aqueous solution used is 110 mL: 10 mL: 140-180 mL; In step B1, aluminum-doped zinc oxide is prepared by co-precipitation, which has n-type semiconductor characteristics. It forms a conductive network through carrier migration and can quickly dissipate surface static charge.

[0009] Step B2: Mix intermediate product 1 with anhydrous ethanol, sonicate for 30 min, add 3-(2,3-epoxypropoxy)propyltrimethoxysilane (KH-560), stir and react in an oil bath at 80°C for 12 h, centrifuge, wash, and vacuum dry to obtain a solid product; under nitrogen protection, mix 1-ethyl-3-hydroxybromopyridine solution and triethylamine, add the above solid product, sonicate for 30 min, stir and reflux at 80°C for 12 h, cool to room temperature, centrifuge, wash, and vacuum dry to obtain intermediate product 2; Furthermore, the ratio of intermediate 1, anhydrous ethanol, KH-560, 1-ethyl-3-hydroxybromopyridine solution, and triethylamine is 0.6 g : 100 mL : 0.6-0.8 g : 8-14 mL : 0.2-0.7 mL; Furthermore, the 1-ethyl-3-hydroxybromopyridine solution is prepared by mixing 1-ethyl-3-hydroxybromopyridine and anhydrous ethanol at a volume ratio of 0.8-1.4 g: 8-14 mL; In step B2, an epoxy group is introduced onto the surface of intermediate product 1, which then undergoes a ring-opening reaction with 1-ethyl-3-hydroxybromopyridine to introduce pyridine bromide into the system. Pyridine bromide can construct a continuous ionic conductive pathway inside the fiber, allowing the accumulated static charge to be rapidly released through directional ion migration, thereby reducing the fiber's volume and surface resistance and preventing static buildup.

[0010] Step B3: Dissolve lithium bis(trifluoromethanesulfonylimide) in deionized water at 50°C to obtain a salt solution. Cool to room temperature, add intermediate product 2, sonicate for 20 min, stir for 8 h, centrifuge, wash, and vacuum dry to obtain modified aluminum-doped zinc oxide. Furthermore, the ratio of lithium bis(trifluoromethanesulfonyl)imide, deionized water, and intermediate 2 is 1.1-1.5 g : 80-100 mL : 0.6 g; In step B3, intermediate product 2 and lithium bis(trifluoromethanesulfonyl)imide undergo an ion exchange reaction. The introduced bis(trifluoromethanesulfonyl)imide ion has a highly delocalized negative charge and its electrostatic binding force with pyridinium cations is much weaker than that with bromide ions. It is easier to dissociate into freely moving ion carriers, significantly improving charge conduction efficiency. In synergy with aluminum-doped zinc oxide, it further enhances the antistatic properties of the fiber.

[0011] A method for preparing a high-strength PET mesh tube includes the following steps: Step S1: Weigh the raw materials according to the weight parts, mix the PET chips, core-shell reinforcing agent, nano-kaolin, triphenyl phosphate, zinc stearate, antioxidant and modified aluminum-doped zinc oxide evenly, melt and extrude to obtain the melt, wherein the extrusion speed is 300-350 r / min and the extrusion processing temperature is 190-220℃; Step S2: Spin the melt at a spinning temperature of 280-290℃ and a spinning speed of 2800-3000m / min. Cool, oil, stretch, shape and wind the melt with a crimp of 9%-13% to obtain fiber filaments. Step S3: Twist the fiber filaments together and weave them in an interlaced manner to obtain a high-strength PET mesh tube.

[0012] The beneficial effects of this invention are: The high-strength PET tubing of this invention can be widely used in automotive wiring harness protection, internal wiring of electronic appliances, communication cable management, and industrial robot tubing wrapping. By introducing a core-shell reinforcing agent and modified aluminum-doped zinc oxide into the PET fiber, the tubing is endowed with excellent comprehensive performance. The core-shell reinforcing agent can effectively absorb impact energy and prevent the propagation of microcracks under stress, thereby significantly improving the tensile strength, tear resistance, and dynamic fatigue resistance of the tubing. At the same time, the modified aluminum-doped zinc oxide gives the tubing efficient and long-lasting antistatic ability, which can dissipate surface static electricity in a timely manner, avoid dust adsorption and electrostatic discharge damage to sensitive electronic components, and ensure the safe operation of equipment.

[0013] The core-shell reinforcing agent of this invention first utilizes 3-mercaptopropyltrimethoxysilane grafted onto the surface of MWCNTs. MWCNTs can improve the strength and elastic modulus of PET fibers. When the fiber is under stress, the stress is transferred from the PET matrix to the MWCNTs, with the MWCNTs bearing the main tensile force. Subsequently, a thiol-olefin click reaction occurs with vinyl-POSS. The introduced POSS molecules can induce PET crystallization, increase the crystallization rate and crystallization temperature, and their steric hindrance can weaken the van der Waals forces between MWCNTs, inhibit MWCNT aggregation, and make them more uniformly dispersed in the PET melt, thereby improving the fiber's fracture toughness while increasing strength. The double bonds on the surface of POSS@MWCNTs undergo a thiol-ene click reaction with 1-thioglycerol. Finally, ethylene glycol and dimethyl terephthalate are used to polymerize PET in situ on the surface of OH-POSS@MWCNTs. The structure is consistent with the PET matrix, and the compatibility is excellent, which helps to eliminate interfacial defects. It works synergistically with POSS and MWCNTs to make the filler more uniform and stable in the PET matrix, ensuring the uniformity of fiber mechanical properties.

[0014] The modified aluminum-doped zinc oxide of this invention is first prepared by co-precipitation, exhibiting n-type semiconductor characteristics. It forms a conductive network through carrier migration, enabling rapid dissipation of surface static charge. Subsequently, epoxy groups are introduced onto its surface, followed by a ring-opening reaction with 1-ethyl-3-hydroxybromopyridine, introducing pyridine bromide into the system. Pyridine bromide can construct continuous ionic conductive pathways within the fiber, allowing accumulated static charge to be rapidly released through directional ion migration, thereby reducing fiber volume and surface resistance and preventing electrostatic accumulation. Finally, an ion exchange reaction is used to introduce highly delocalized bis(trifluoromethanesulfonyl)imide ions, whose electrostatic binding force with pyridinium cations is much weaker than that with bromide ions, making it easier to dissociate freely moving ion carriers. This significantly improves charge conduction efficiency, synergistically enhancing the antistatic properties of the fiber in conjunction with the aluminum-doped zinc oxide. Detailed Implementation

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] The MWCNTs treated with mixed acid in the examples were prepared by the following steps: Mix 60 mL of concentrated sulfuric acid and 20 mL of concentrated nitric acid to obtain a mixed acid. Pour the mixed acid into 2 g of MWCNTs, sonicate for 20 min, stir in a 60 °C water bath for 3 h, then dilute tenfold and let stand for 12 h. Remove the supernatant, filter, wash, and vacuum dry for later use.

[0017] Example 1: The core-shell reinforcing agent was prepared by the following steps: Step A1: Mix the acid-treated MWCNTs with anhydrous ethanol, sonicate for 20 min, purge with nitrogen for 5 min, then add glacial acetic acid and 3-mercaptopropyltrimethoxysilane dropwise while stirring, and react at room temperature for 24 h. After the reaction is complete, add acetone and continue to react under a nitrogen atmosphere for 6 h. Then filter, wash, and vacuum dry to obtain SH-MWCNTs. The ratio of MWCNTs, anhydrous ethanol, glacial acetic acid, 3-mercaptopropyltrimethoxysilane and acetone is 0.4 g: 100 mL: 4 mL: 8 mL: 100 mL. Step A2: Add the vinyl-POSS solution to SH-MWCNTs, then add AIBN, stir, bubble with nitrogen for 20 min, heat to 80°C in an oil bath, stir and react for 8 h under nitrogen protection, cool to room temperature, filter, wash successively with toluene and anhydrous methanol, and dry under vacuum to obtain POSS@MWCNTs. The vinyl-POSS solution is prepared by mixing vinyl-POSS and toluene in a volume ratio of 0.1 g: 20 mL. The volume ratio of vinyl-POSS solution, SH-MWCNTs, AIBN, toluene and anhydrous methanol is 20 mL: 0.4 g: 0.0015 g: 20 mL: 15 mL. Step A3: Mix POSS@MWCNTs and toluene, add 1-thioglycerol and AIBN, react at 80°C for 12 h under nitrogen protection, cool to room temperature, filter, wash, and vacuum dry to obtain OH-POSS@MWCNTs. The ratio of POSS@MWCNTs, toluene, 1-thioglycerol and AIBN is 0.4 g: 20 mL: 0.2 g: 1.5 mg. Step A4: Mix OH-POSS@MWCNTs and ethylene glycol, sonicate for 5 min, then add dimethyl terephthalate and zinc acetate catalyst, stir and heat to 185℃ for reaction, react for 3 h, add antimony trioxide condensation catalyst, continue heating to 200℃, evacuate to 15 Pa, keep at this temperature for 1 h, then raise the temperature to 285℃ for condensation, stop the reaction when the system viscosity reaches 0.7 dL / g, cool, wash with anhydrous ethanol, and vacuum dry to obtain the core-shell reinforcing agent. The ratio of OH-POSS@MWCNTs, ethylene glycol, dimethyl terephthalate, zinc acetate, antimony trioxide and anhydrous ethanol is 0.4 g: 13 mL: 0.4 g: 0.004 g: 0.004 g: 30 mL.

[0018] Modified aluminum-doped zinc oxide is prepared by the following steps: Step B1: Prepare 0.15 mol / L zinc sulfate aqueous solution, 0.15 mol / L aluminum ammonium sulfate aqueous solution, and 0.45 mol / L ammonium bicarbonate aqueous solution respectively. Under the conditions of stirring, reaction temperature of 50℃, and pH of reaction solution of 7, add ammonium bicarbonate aqueous solution to aluminum ammonium sulfate aqueous solution, followed by zinc sulfate aqueous solution. After aging for 12 h, filter, wash, dry, grind, and then put into a muffle furnace and keep at 500℃ for 2 h to obtain intermediate product 1. The ratio of zinc sulfate aqueous solution, aluminum ammonium sulfate aqueous solution and ammonium bicarbonate aqueous solution is 110 mL: 10 mL: 140 mL. Step B2: Mix intermediate product 1 with anhydrous ethanol, sonicate for 30 min, add KH-560, stir and react in an oil bath at 80℃ for 12 h, centrifuge, wash, and vacuum dry to obtain a solid product; under nitrogen protection, mix 1-ethyl-3-hydroxybromopyridine solution and triethylamine, add the above solid product, sonicate for 30 min, stir and reflux at 80℃ for 12 h, cool to room temperature, centrifuge, wash, and vacuum dry to obtain intermediate product 2. The ratio of intermediate product 1, anhydrous ethanol, KH-560, 1-ethyl-3-hydroxybromopyridine solution, and triethylamine is 0.6 g: 100 mL: 0.6 g: 8 mL: 0.2 mL. The 1-ethyl-3-hydroxybromopyridine solution is prepared by mixing 1-ethyl-3-hydroxybromopyridine and anhydrous ethanol at a ratio of 0.8 g: 8 mL. Step B3: Dissolve lithium bis(trifluoromethanesulfonyl)imide in deionized water at 50°C to obtain a salt solution. Cool to room temperature, add intermediate product 2, sonicate for 20 min, stir for 8 h, centrifuge, wash, and vacuum dry to obtain modified aluminum-doped zinc oxide. The ratio of lithium bis(trifluoromethanesulfonyl)imide, deionized water, and intermediate product 2 is 1.1 g: 80 mL: 0.6 g.

[0019] Example 2: The core-shell reinforcing agent was prepared by the following steps: Step A1: Mix the acid-treated MWCNTs with anhydrous ethanol, sonicate for 20 min, purge with nitrogen for 5 min, then add glacial acetic acid and 3-mercaptopropyltrimethoxysilane dropwise while stirring, and react at room temperature for 24 h. After the reaction is complete, add acetone and continue to react under a nitrogen atmosphere for 6 h. Then filter, wash, and vacuum dry to obtain SH-MWCNTs. The ratio of MWCNTs, anhydrous ethanol, glacial acetic acid, 3-mercaptopropyltrimethoxysilane and acetone is 0.4 g: 100 mL: 4.5 mL: 9 mL: 110 mL. Step A2: Add the vinyl-POSS solution to SH-MWCNTs, then add AIBN, stir, bubble with nitrogen for 20 min, heat to 80°C in an oil bath, stir and react for 8 h under nitrogen protection, cool to room temperature, filter, wash successively with toluene and anhydrous methanol, and dry under vacuum to obtain POSS@MWCNTs. The vinyl-POSS solution is prepared by mixing vinyl-POSS and toluene in a volume ratio of 0.15 g: 25 mL. The volume ratio of vinyl-POSS solution, SH-MWCNTs, AIBN, toluene and anhydrous methanol is 25 mL: 0.4 g: 0.002 g: 30 mL: 20 mL. Step A3: Mix POSS@MWCNTs and toluene, add 1-thioglycerol and AIBN, react at 80°C for 12 h under nitrogen protection, cool to room temperature, filter, wash, and vacuum dry to obtain OH-POSS@MWCNTs. The ratio of POSS@MWCNTs, toluene, 1-thioglycerol and AIBN is 0.4 g: 25 mL: 0.3 g: 2 mg. Step A4: Mix OH-POSS@MWCNTs and ethylene glycol, sonicate for 5 min, then add dimethyl terephthalate and zinc acetate catalyst, stir and heat to 185℃ for reaction, react for 3 h, add antimony trioxide condensation catalyst, continue heating to 200℃, evacuate to 15 Pa, keep at this temperature for 1 h, then raise the temperature to 285℃ for condensation, stop the reaction when the system viscosity reaches 0.7 dL / g, cool, wash with anhydrous ethanol, and vacuum dry to obtain the core-shell reinforcing agent. The ratio of OH-POSS@MWCNTs, ethylene glycol, dimethyl terephthalate, zinc acetate, antimony trioxide and anhydrous ethanol is 0.4 g: 14 mL: 0.45 g: 0.0045 g: 0.0045 g: 40 mL.

[0020] Modified aluminum-doped zinc oxide is prepared by the following steps: Step B1: Prepare 0.15 mol / L zinc sulfate aqueous solution, 0.15 mol / L aluminum ammonium sulfate aqueous solution, and 0.45 mol / L ammonium bicarbonate aqueous solution respectively. Under the conditions of stirring, reaction temperature of 50℃, and pH of reaction solution of 7, add ammonium bicarbonate aqueous solution to aluminum ammonium sulfate aqueous solution, followed by zinc sulfate aqueous solution. After aging for 12 h, filter, wash, dry, grind, and then put into a muffle furnace and keep at 500℃ for 2 h to obtain intermediate product 1. The ratio of zinc sulfate aqueous solution, aluminum ammonium sulfate aqueous solution and ammonium bicarbonate aqueous solution is 110 mL: 10 mL: 160 mL. Step B2: Mix intermediate product 1 with anhydrous ethanol, sonicate for 30 min, add KH-560, stir and react in an oil bath at 80℃ for 12 h, centrifuge, wash, and vacuum dry to obtain a solid product; under nitrogen protection, mix 1-ethyl-3-hydroxybromopyridine solution and triethylamine, add the above solid product, sonicate for 30 min, stir and reflux at 80℃ for 12 h, cool to room temperature, centrifuge, wash, and vacuum dry to obtain intermediate product 2. The ratio of intermediate product 1, anhydrous ethanol, KH-560, 1-ethyl-3-hydroxybromopyridine solution and triethylamine is 0.6 g: 100 mL: 0.7 g: 11 mL: 0.4 mL. The 1-ethyl-3-hydroxybromopyridine solution is prepared by mixing 1-ethyl-3-hydroxybromopyridine and anhydrous ethanol at a ratio of 1.1 g: 11 mL. Step B3: Dissolve lithium bis(trifluoromethanesulfonyl)imide in deionized water at 50°C to obtain a salt solution. Cool to room temperature, add intermediate product 2, sonicate for 20 min, stir for 8 h, centrifuge, wash, and vacuum dry to obtain modified aluminum-doped zinc oxide. The ratio of lithium bis(trifluoromethanesulfonyl)imide, deionized water, and intermediate product 2 is 1.3 g: 90 mL: 0.6 g.

[0021] Example 3: The core-shell reinforcing agent was prepared by the following steps: Step A1: Mix the acid-treated MWCNTs with anhydrous ethanol, sonicate for 20 min, purge with nitrogen for 5 min, then add glacial acetic acid and 3-mercaptopropyltrimethoxysilane dropwise while stirring, and react at room temperature for 24 h. After the reaction is complete, add acetone and continue to react under a nitrogen atmosphere for 6 h. Then filter, wash, and vacuum dry to obtain SH-MWCNTs. The ratio of MWCNTs, anhydrous ethanol, glacial acetic acid, 3-mercaptopropyltrimethoxysilane and acetone is 0.4 g: 100 mL: 5 mL: 10 mL: 120 mL. Step A2: Add the vinyl-POSS solution to SH-MWCNTs, then add AIBN, stir, bubble with nitrogen for 20 min, heat to 80°C in an oil bath, stir and react for 8 h under nitrogen protection, cool to room temperature, filter, wash successively with toluene and anhydrous methanol, and vacuum dry to obtain POSS@MWCNTs. The vinyl-POSS solution is prepared by mixing vinyl-POSS and toluene in a volume ratio of 0.2 g: 30 mL. The volume ratio of vinyl-POSS solution, SH-MWCNTs, AIBN, toluene and anhydrous methanol is 30 mL: 0.4 g: 0.0025 g: 40 mL: 30 mL. Step A3: Mix POSS@MWCNTs and toluene, add 1-thioglycerol and AIBN, react at 80°C for 12 h under nitrogen protection, cool to room temperature, filter, wash, and vacuum dry to obtain OH-POSS@MWCNTs. The ratio of POSS@MWCNTs, toluene, 1-thioglycerol and AIBN is 0.4 g: 30 mL: 0.4 g: 3 mg. Step A4: Mix OH-POSS@MWCNTs and ethylene glycol, sonicate for 5 min, then add dimethyl terephthalate and zinc acetate catalyst, stir and heat to 185℃ for reaction, react for 3 h, add antimony trioxide condensation catalyst, continue heating to 200℃, evacuate to 15 Pa, keep at this temperature for 1 h, then raise the temperature to 285℃ for condensation, stop the reaction when the system viscosity reaches 0.7 dL / g, cool, wash with anhydrous ethanol, and vacuum dry to obtain the core-shell reinforcing agent. The ratio of OH-POSS@MWCNTs, ethylene glycol, dimethyl terephthalate, zinc acetate, antimony trioxide and anhydrous ethanol is 0.4 g: 15 mL: 0.5 g: 0.005 g: 0.005 g: 50 mL.

[0022] Modified aluminum-doped zinc oxide is prepared by the following steps: Step B1: Prepare 0.15 mol / L zinc sulfate aqueous solution, 0.15 mol / L aluminum ammonium sulfate aqueous solution, and 0.45 mol / L ammonium bicarbonate aqueous solution respectively. Under the conditions of stirring, reaction temperature of 50℃, and pH of reaction solution of 7, add ammonium bicarbonate aqueous solution to aluminum ammonium sulfate aqueous solution, followed by zinc sulfate aqueous solution. After aging for 12 h, filter, wash, dry, grind, and then put into a muffle furnace and keep at 500℃ for 2 h to obtain intermediate product 1. The ratio of zinc sulfate aqueous solution, aluminum ammonium sulfate aqueous solution and ammonium bicarbonate aqueous solution is 110 mL: 10 mL: 180 mL. Step B2: Mix intermediate product 1 with anhydrous ethanol, sonicate for 30 min, add KH-560, stir and react in an oil bath at 80℃ for 12 h, centrifuge, wash, and vacuum dry to obtain a solid product; under nitrogen protection, mix 1-ethyl-3-hydroxybromopyridine solution and triethylamine, add the above solid product, sonicate for 30 min, stir and reflux at 80℃ for 12 h, cool to room temperature, centrifuge, wash, and vacuum dry to obtain intermediate product 2. The ratio of intermediate product 1, anhydrous ethanol, KH-560, 1-ethyl-3-hydroxybromopyridine solution, and triethylamine is 0.6 g: 100 mL: 0.8 g: 14 mL: 0.7 mL. The 1-ethyl-3-hydroxybromopyridine solution is prepared by mixing 1-ethyl-3-hydroxybromopyridine and anhydrous ethanol at a ratio of 1.4 g: 14 mL. Step B3: Dissolve lithium bis(trifluoromethanesulfonyl)imide in deionized water at 50°C to obtain a salt solution. Cool to room temperature, add intermediate product 2, sonicate for 20 min, stir for 8 h, centrifuge, wash, and vacuum dry to obtain modified aluminum-doped zinc oxide. The ratio of lithium bis(trifluoromethanesulfonyl)imide, deionized water, and intermediate product 2 is 1.5 g: 100 mL: 0.6 g.

[0023] Example 4: A method for preparing a high-strength PET mesh tube, comprising the following steps: 60 PET slices, 8 parts of the core-shell reinforcing agent prepared in Example 1, 2 parts of nano-kaolin, 1 part of triphenyl phosphate, 3 parts of zinc stearate, 0.5 parts of antioxidant 1010, and 1 part of modified aluminum-doped zinc oxide prepared in Example 1. Step S1: Weigh the raw materials according to the weight parts, mix the PET slices, the core-shell reinforcing agent prepared in Example 1, nano-kaolin, triphenyl phosphate, zinc stearate, antioxidant 1010 and the modified aluminum-doped zinc oxide prepared in Example 1 evenly, melt and extrude to obtain a melt, wherein the extrusion speed is 300 r / min and the extrusion processing temperature is 190℃. Step S2: Spin the melt at a spinning temperature of 280℃ and a spinning speed of 2800m / min. Cool, oil, stretch, shape and wind the melt with a crimp of 9% to obtain fiber filaments. Step S3: Twist the fiber filaments together and weave them in an interlaced manner to obtain a high-strength PET mesh tube.

[0024] Example 5: A method for preparing a high-strength PET mesh tube, comprising the following steps: 70 PET slices, 11 parts of the core-shell reinforcing agent prepared in Example 2, 3 parts of nano-kaolin, 1.5 parts of triphenyl phosphate, 4 parts of zinc stearate, 0.5 parts of antioxidant 168, 0.5 parts of antioxidant 1076, and 2 parts of modified aluminum-doped zinc oxide prepared in Example 2. Step S1: Weigh the raw materials according to the weight parts, mix the PET slices, the core-shell reinforcing agent prepared in Example 2, nano-kaolin, triphenyl phosphate, zinc stearate, antioxidant 168, antioxidant 1076 and the modified aluminum-doped zinc oxide prepared in Example 2 evenly, melt and extrude to obtain a melt, wherein the extrusion speed is 350 r / min and the extrusion processing temperature is 200℃; Step S2: Spin the melt at a spinning temperature of 285℃ and a spinning speed of 2900m / min. Cool, oil, stretch, shape and wind the melt with a crimp of 11% to obtain fiber filaments. Step S3: Twist the fiber filaments together and weave them in an interlaced manner to obtain a high-strength PET mesh tube.

[0025] Example 6: A method for preparing a high-strength PET mesh tube, comprising the following steps: 80 PET slices, 15 parts of the core-shell reinforcing agent prepared in Example 3, 4 parts of nano-kaolin, 2 parts of triphenyl phosphate, 6 parts of zinc stearate, 0.5 parts of antioxidant 1010, 0.5 parts of antioxidant 1076, and 3 parts of modified aluminum-doped zinc oxide prepared in Example 3. Step S1: Weigh the raw materials according to the weight parts, mix the PET slices, the core-shell reinforcing agent prepared in Example 3, nano-kaolin, triphenyl phosphate, zinc stearate, antioxidant 1010, antioxidant 1076 and the modified aluminum-doped zinc oxide prepared in Example 3 evenly, melt and extrude to obtain a melt, wherein the extrusion speed is 350 r / min and the extrusion processing temperature is 220℃; Step S2: Spin the melt at a spinning temperature of 290℃ and a spinning speed of 3000m / min. Cool, oil, stretch, shape and wind the melt with a crimp of 13% to obtain fiber filaments. Step S3: Twist the fiber filaments together and weave them in an interlaced manner to obtain a high-strength PET mesh tube.

[0026] Comparative Example 1: This comparative example is a PET mesh tube, which differs from Example 6 in that MWCNTs are used instead of the core-shell toughening agent prepared in Example 3, and all other aspects are the same.

[0027] Comparative Example 2: This comparative example is a PET mesh tube, which differs from Example 6 in that zinc oxide is used instead of the modified aluminum-doped zinc oxide prepared in Example 3, and all other aspects are the same.

[0028] Comparative Example 3: This comparative example is a PET mesh tube. The difference between this example and Example 6 is that MWCNTs are used instead of the core-shell toughening agent prepared in Example 3, and zinc oxide is used instead of the modified aluminum-doped zinc oxide prepared in Example 3. All other aspects are the same.

[0029] The PET fibers prepared in Examples 4-6 and Comparative Examples 1-3 were subjected to performance tests: The fineness, strength, and elongation at break of the fibers were tested according to GB / T 14337-2022, Test Method for Tensile Properties of Short Chemical Fibers. The antistatic performance was tested using a fiber resistivity meter. After drying the fiber with degreasing agent, 15g of fiber was weighed and its volume resistivity was measured. The volume resistivity (ρ) was calculated according to the formula: ρ=Rbhf / L, where R is the average resistance of the fiber; b is the effective length of the electrode plate; h is the height of the electrode plate; L is the distance between the two electrode plates; and f is the standard filling degree of the fiber.

[0030] The test results are shown in Table 1: Table 1: Performance Test Results

[0031] As can be seen from Table 1, the PET mesh tube prepared by the present invention has excellent mechanical properties. The fiber fineness prepared in Example 6 is 6.5 dtex, the fiber strength can reach 6.7 cN / dtex, and the elongation at break is 27%, which is significantly improved compared with Comparative Example 1, indicating that the core-shell toughening agent of the present invention improves the fiber strength. As can be seen from Comparative Example 2 and Example 6, the modified aluminum-doped zinc oxide prepared by the present invention reduces the volume resistivity of the fiber, indicating that the modified aluminum-doped zinc oxide imparts excellent antistatic properties to the fiber.

[0032] The above content is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the scope defined by the inventive concept, they should all fall within the protection scope of the present invention.

Claims

1. A high-strength PET mesh tube, characterized in that, The raw materials include the following parts by weight: 60-80 parts PET chips, 8-15 parts core-shell reinforcing agent, 2-4 parts nano kaolin, 1-2 parts triphenyl phosphate, 3-6 parts zinc stearate, 0.5-1 part antioxidant, and 1-3 parts modified aluminum-doped zinc oxide. The core-shell reinforcing agent is prepared by the following steps: Step A1: Mix the acid-treated MWCNTs with anhydrous ethanol, sonicate for 20 min, purge with nitrogen for 5 min, then add glacial acetic acid and 3-mercaptopropyltrimethoxysilane dropwise while stirring, and react at room temperature for 24 h. After the reaction is complete, add acetone and continue to react under nitrogen atmosphere for 6 h. Then filter, wash, and vacuum dry to obtain SH-MWCNTs. Step A2: Add the vinyl-POSS solution to SH-MWCNTs, then add AIBN, stir, bubble with nitrogen for 20 min, heat to 80°C in an oil bath, stir and react for 8 h under nitrogen protection, cool to room temperature, filter, wash with toluene and anhydrous methanol successively, and dry under vacuum to obtain POSS@MWCNTs; Step A3: Mix POSS@MWCNTs and toluene, add 1-thioglycerol and AIBN, react at 80°C for 12 h under nitrogen protection, cool to room temperature, filter, wash, and vacuum dry to obtain OH-POSS@MWCNTs; Step A4: Mix OH-POSS@MWCNTs and ethylene glycol, sonicate for 5 min, then add dimethyl terephthalate and zinc acetate catalyst, stir and heat to 185℃ for reaction, react for 3 h, add antimony trioxide condensation catalyst, continue heating to 200℃, evacuate to 15 Pa, keep at this temperature for 1 h, then raise the temperature to 285℃ for condensation, stop the reaction when the system viscosity reaches 0.7 dL / g, cool, wash with anhydrous ethanol, and vacuum dry to obtain the core-shell reinforcing agent.

2. The high-strength PET mesh tube according to claim 1, characterized in that, In step A1, the ratio of MWCNTs, anhydrous ethanol, glacial acetic acid, 3-mercaptopropyltrimethoxysilane, and acetone is 0.4g:100mL:4-5mL:8-10mL:100-120mL.

3. A high-strength PET mesh tube according to claim 1, characterized in that, In step A2, the vinyl-POSS solution is prepared by mixing vinyl-POSS and toluene in a volume ratio of 0.1-0.2g: 20-30mL. The volume ratio of vinyl-POSS solution, SH-MWCNTs, AIBN, toluene and anhydrous methanol is 20-30mL: 0.4g: 0.0015-0.0025g: 20-40mL: 15-30mL.

4. A high-strength PET mesh tube according to claim 1, characterized in that, In step A3, the ratio of POSS@MWCNTs, toluene, 1-thioglycerol and AIBN is 0.4g: 20-30mL: 0.2-0.4g: 1.5-3mg.

5. A high-strength PET mesh tube according to claim 1, characterized in that, In step A4, the ratio of OH-POSS@MWCNTs, ethylene glycol, dimethyl terephthalate, zinc acetate, antimony trioxide, and anhydrous ethanol is 0.4g: 13-15mL: 0.4-0.5g: 0.004-0.005g: 0.004-0.005g: 30-50mL.

6. A high-strength PET mesh tube according to claim 1, characterized in that, The modified aluminum-doped zinc oxide is prepared by the following steps: Step B1: Prepare 0.15 mol / L zinc sulfate aqueous solution, 0.15 mol / L aluminum ammonium sulfate aqueous solution and 0.45 mol / L ammonium bicarbonate aqueous solution respectively. Under the conditions of stirring, reaction temperature of 50℃ and pH of reaction solution of 7, add ammonium bicarbonate aqueous solution to aluminum ammonium sulfate aqueous solution, followed by zinc sulfate aqueous solution. After aging for 12 h, filter, wash, dry, grind, and then put into a muffle furnace and keep at 500℃ for 2 h to obtain intermediate product 1. Step B2: Mix intermediate product 1 with anhydrous ethanol, sonicate for 30 min, add KH-560, stir and react in an oil bath at 80℃ for 12 h, centrifuge, wash, and vacuum dry to obtain a solid product; under nitrogen protection, mix 1-ethyl-3-hydroxybromopyridine solution and triethylamine, add the above solid product, sonicate for 30 min, stir and reflux at 80℃ for 12 h, cool to room temperature, centrifuge, wash, and vacuum dry to obtain intermediate product 2; Step B3: Dissolve lithium bis(trifluoromethanesulfonylimide) in deionized water at 50°C to obtain a salt solution. Cool to room temperature, add intermediate product 2, sonicate for 20 min, stir for 8 h, centrifuge, wash, and vacuum dry to obtain modified aluminum-doped zinc oxide.

7. A high-strength PET mesh tube according to claim 6, characterized in that, In step B1, the ratio of zinc sulfate aqueous solution, aluminum ammonium sulfate aqueous solution, and ammonium bicarbonate aqueous solution is 110 mL: 10 mL: 140-180 mL.

8. A high-strength PET mesh tube according to claim 6, characterized in that, The ratio of intermediate product 1, anhydrous ethanol, KH-560, 1-ethyl-3-hydroxybromopyridine solution, and triethylamine in step B2 is 0.6 g: 100 mL: 0.6-0.8 g: 8-14 mL: 0.2-0.7 mL. The 1-ethyl-3-hydroxybromopyridine solution is prepared by mixing 1-ethyl-3-hydroxybromopyridine and anhydrous ethanol in a ratio of 0.8-1.4 g: 8-14 mL.

9. A high-strength PET mesh tube according to claim 6, characterized in that, In step B3, the ratio of lithium bis(trifluoromethanesulfonylimide), deionized water, and intermediate 2 is 1.1-1.5 g: 80-100 mL: 0.6 g.

10. A method for preparing a high-strength PET mesh tube according to any one of claims 1-9, characterized in that, Prepared by the following steps: Step S1: Weigh the raw materials according to the weight parts, mix the PET chips, core-shell reinforcing agent, nano-kaolin, triphenyl phosphate, zinc stearate, antioxidant and modified aluminum-doped zinc oxide evenly, melt and extrude to obtain the melt, wherein the extrusion speed is 300-350 r / min and the extrusion processing temperature is 190-220℃; Step S2: Spin the melt at a spinning temperature of 280-290℃ and a spinning speed of 2800-3000m / min. Cool, oil, stretch, shape and wind the melt with a crimp of 9%-13% to obtain fiber filaments. Step S3: Twist the fiber filaments together and weave them in an interlaced manner to obtain a high-strength PET mesh tube.